The statist industrialization and the formation of industrial working class in the early republic - Dingiloğlu, Selin. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
The basic concern of this master’s thesis is to develop a historical approach towards the statist industrialization initiated in early 1930s and the formation of Turkish industrial working class with its economic, social, ideological and political aspects. It tries to ascertain how the stateowned enterprises Sümerbank and Etibank shaped the profile of the industrial working class and what sort of an influence they had on the intra-class composition and inter-class relations. Those state-owned factories went beyond being merely a production plant and provided other facilities such as housing, training activities, and so on. In this way, the industry complexes contributed to the provisioning and the reproduction of the labour force required by the statist industrialization. The policies pursued by those enterprises had an impact also on the formation and representation of the class identity of industrial workers. Depicting how those impacts were experienced by workers, this thesis examines the labor movement, including both the period before and after the ban on unionization.
Keywords: Government business enterprises -- Turkey.; Working class -- Turkey.